Anterior Palatal Fistula Formation after Le Fort I Osteotomy in Conventional Orthognathic Surgery - Saeed Nezafati; Tannaz Pourlak (Case Reports in Dentistry)
The prevalence rate of maxillary ischemic complications following Le Fort I osteotomy was estimated to be about 1%. Understanding the local and systemic factors affecting maxillary perfusion before, during, and after the surgery can prevent the development of these complications. The present study investigated a case of anterior palatal fistula following the classic Le Fort I osteotomy.